Carbohydrate response element‐binding protein regulates lipid metabolism via mTOR complex1 in diabetic nephropathy. Issue 1 (24th June 2020) - Chen, Nan; Mu, Lin; Yang, Zhifen; Du, Chunyang; Wu, Ming; Song, Shan; Yuan, Chen; Shi, Yonghong
Abstract: Lipid deposition caused by the disorder of renal lipid metabolism is involved in diabetic nephropathy (DN). Carbohydrate response element‐binding protein (ChREBP) is a key transcription factor in high glucose‐induced cellular fat synthesis. At present, the regulation and mechanism of ChREBP on fat metabolism in diabetic kidneys are still unclear. In this study, we showed that lack of ChREBP significantly improved renal injury, inhibited oxidative stress, lipid deposition, fatty acid synthase (FASN), acetyl‐CoA carboxylase (ACC) and thioredoxin‐interacting protein (TXNIP) expression, as well as the activity of mammalian target of rapamycin complex 1 (mTORC1) in diabetic kidneys. Meanwhile, ChREBP deficiency upregulated the expression of peroxisome proliferator‐activated receptor‐α (PPARα), carnitine palmitoyltransferaser 1A (CPT1A) and acyl‐coenzyme A oxidase 1 (ACOX1) in diabetic kidneys. In vitro, knockdown of ChREBP attenuated lipid deposition, mTORC1 activation, and expression of FASN and ACC, increased PPARα, CPT1A, and ACOX1 expression in HK‐2 cells and podocytes under high glucose (HG) conditions. Moreover, HG‐induced lipid deposition, increased expression of FASN and ACC and decreased expression of PPARα, CPT1A, and ACOX1 were reversed by rapamycin, a specific inhibitor of mTORC1, in HK‐2 cells. These results indicate that ChREBP deficiency alleviates diabetes‐associated renal lipid accumulation by inhibiting mTORC1 activity and suggest that reduction of ChREBP is a potential therapeutic strategy to treat DN. Abstract : In this study, we showed that lack of carbohydrate response element‐binding protein (ChREBP) significantly improved renal injury, inhibited oxidative stress, lipid deposition, expression of fatty acid synthase (FASN), and acetyl‐CoA carboxylase (ACC) as well as the activity of mammalian target of rapamycin complex 1 (mTORC1) in diabetic kidneys. ChREBP deficiency upregulated the expression of peroxisome proliferator‐activated receptor‐α (PPARα), carnitine palmitoyltransferaser 1A (CPT1A), and acyl‐coenzyme A oxidase 1 (ACOX1) in diabetic kidneys. In vitro, ChREBP deficiency reduced renal lipid accumulation by inhibiting fatty acid synthesis and promoting lipolytic enzyme through inhibiting mTORC1 activation in HK‐2 cells and podocytes.